GPU-based Electromagnetic Optimization of MIMO Channels - Alfonso Breglia; Amedeo Capozzoli; Claudio Curcio; Salvatore Di Donna; Angelo Liseno (Applied Computational Electromagnetics Society Journal (ACES), 2021)
Strategies to accelerate MIMO channel capacity optimization on GPUs are outlined. The optimization scheme is dealt with by properly facing the main computational issues. In particular, the propagation environment is described by ultrafast Geometrical Optics (GO), singular values are computed by a very fast scheme and the optimizer is a parallel version of the differential evolutionary algorithm. The unknowns are given proper representations to reduce the number of optimization parameters.